1986
DOI: 10.1007/bf02427276
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of retinopathy in children and adolescents with Type 1 (insulin-dependent) diabetes mellitus

Abstract: In our preceding paper, the prevalence and development of retinopathy in 231 Type 1 diabetic children and adolescents were reported to be associated with the duration of diabetes and its age at onset. This paper analyses the relationships between the development of retinopathy and the following factors: age, sex, puberty, blood pressure, insulin dosage, HLA antigens, long-term glycaemic control, and serum cholesterol and triglycerides. All these variables were longitudinally evaluated in a cohort of 322 insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 19 publications
7
52
1
Order By: Relevance
“…No significant difference was found between the sexes in the incidence of any retinopathy, background retinopathy and proliferative retinopathy. This is in concordance with other incidence studies (Weber et al 1986;Klein et al 1989a). …”
Section: Icelandsupporting
confidence: 94%
“…No significant difference was found between the sexes in the incidence of any retinopathy, background retinopathy and proliferative retinopathy. This is in concordance with other incidence studies (Weber et al 1986;Klein et al 1989a). …”
Section: Icelandsupporting
confidence: 94%
“…Dornans group did not find any relationship between serum triglyceride levels and severity of retinopathy in insulindependent diabetic patients (Dornan et al 1982) and a study by Agardh (1988), gave the same results. On the other hand, Weber et al found that serum triglycerides were strongly associated with degree of retinopathy in children and adolescents with diabetes mellitus type 1 (Weber et al 1986). Other studies (Eckel et al 1981;West et al 1980) support the latter finding with a relationship between higher levels of triglycerides and more severe retinopathy.…”
Section: Discussionmentioning
confidence: 98%
“…Serum cholesterol levels were in some studies found to correlate to more severe retinopathy (Dornan et al 1982;Eckel et al 1981;Mouton & Gill 1988 ;Scanu & Fless 1990;Weber et al 1986) while in other studies such a relationship was not found (Weber et al 1986;West et al 1980). Dornan et al (1982) measured serum lipid levels in small groups of insulin-dependent diabetic patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the introduction of HbAlc as a reliable measure of long-term blood glucose control, several studies confirmed this association [12][13][14][15][16][17]. In the Wisconsin study [12], a clear relationship between one single HbAlc measurement and the progression of retinopathy during the following 10 years was demonstrated.…”
Section: Epidemiological Studiesmentioning
confidence: 94%